Spurring Space Industry Development in Malaysia: the Enabling Capabilities (Journal of Science, Technology and Innovation Policy, 2021)
Malaysia’s endeavour to a space program is an important milestone in carving our very own niche in the space sector. This initiative can act as a catalyst, not only to the space industry, but also to the existing thriving local aerospace sector in the country. Science, technology and innovation are the main drivers that will move our nation’s economy forward. Aspects of these enabling capabilities are especially important to the development of the space industry, and are priorities for the success of Malaysia’s space initiative. The authors have identified five specific existing enablers that has Malaysia possessed in order to succeed in this highly competitive business. These enablers are; Supportive Government Policies; Strong and Developed Infrastructures; Innovative Financing Schemes; Vibrant Business Climate; and High Quality of Life. However, this study cautions that these enablers will only facilitate our space endeavour, but not necessarily ensure its success. This paper also dwells on the issue that these factors are not only important enablers to the space industry, but also can be promoters of innovative ideas and applications. Sometimes this is perceived as pushing technology, when, in fact, the entire system works together to provide solutions to delivery policy problems.
Keywords: Malaysia space industry